Employee Performance Based On Leadership and Discipline at CV. Wina Purnama Pamulang South Tangerang - Ellesia, Nindie; Sunarto, Ading; Mundariyah, Siti Khotijah (SAINTIS Publishing, 2022)
This study aims to determine the effect of leadership and discipline on employee performance at CV. Wina Cahaya Purnama, Pamulang, South Tangerang. The research method used is descriptive quantitative with a total sample population of 53 respondents. Methods of data collection by using a questionnaire. The analysis used includes: validity test, reliability test, classical assumption test, correlation coefficient test, coefficient of determination test, t-test and F-test. Based on the results of the study obtained multiple linear regression equation Y = 7.097 + 0.245 X1 + 0.592 X2. With a coefficient of determination of 0.655, it means that both variables have an effect on employee performance. Hypothesis testing shows that partially or simultaneously leadership and discipline affect the performance of CV employees. Wina Cahaya Purnama, Pamulang, South Tangerang.